The Effectiveness of a Critical Literacy Model to Improve Students’ Critical Literacy Skills - Diyah Ayu Rizqiani; Sri Yuliani; Roziah Roziah; Al Malikul Ikhwanda Putra (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the current era of media saturation, the emphasis on teaching reading is on cultivating students' critical literacy abilities. This enables them to examine the specific social and political biases conveyed by an author and form a critical perspective on the topics addressed in a text. The objective of this study is to evaluate the efficacy of a critical literacy model in enhancing students' critical literacy abilities during English as a Foreign Language (EFL) Reading classes. A quantitative analytic method was employed for experimental study. The study was conducted in the English Language Education Study Program at a private university situated in Yogyakarta. There were 20 students in the sampling. The individuals in question were students in their fifth semester who enroll in the Critical Reading Class during the Odd Semester of the Academic Year 2022/2023. The data were acquired through the methods of observation, questionnaire administration, interviews, and reading assessments. The study's findings showed that the model was effective, as evidenced by the results of the independent T test indicate a statistically significant difference, with a significance level (two-tailed) below 0.05. In addition, the scores of the pre-test and post-tests in the experimental class surpassed those in the control class. The experimental group demonstrated a substantial improvement in their post-test score, achieving a gain of 3.64 points. In summary, the implementation of the critical literacy framework yielded significant improvements in students' critical literacy skills across various dimensions, including precision, coherence, profundity, analysis, and the identification of latent implications.